Das erlösende Wort: Between Wittgenstein and Broch - Bon, Emma Lavinia (Scenari, 2022)
The purpose of this contribution is to deepen the relationship between language and the unspeakable by intertwining a literary work – Hermann Broch’s Der Tod des Vergil – and a philosophical work – Ludwig Wittgenstein’s Tractatus logico-philosophicus. In the first case, the unspeakable is identified with the very core of the real, with the genetic process of the world that incessantly evades the linguistic representations and the significant structures aimed at expressing it. In the second case, although world and language share the same structure, and therefore language can express the facts of the world, what escapes the sayable is the condition of possibility of this structure, the ‘logical form’ that is common to both. For both Wittgenstein and Broch, language is incessantly confronted with something that remains unsignifiable, but which, insofar as that which exceeds the signified – the world or logical form – is at the same time the condition of possibility of signification, is exposed in every phrase: the work then becomes an image of the unspeakable that shows itself, reflecting it on its surface.